Gender Equity in Hadith Literature: An Analysis of the Contemporary Hadith Curriculum of Madrasah Aliyah in Indonesia - Arifin, Tajul (วารสารอิสลามศึกษา มหาวิทยาลัยสงขลานครินทร์, 2019)
This paper was stimulated by the fact that Muslim women participation in education in Indonesia is still lower than that in neighbouring’s countries. This condition has been influenced by the weak support of Hadith Curriculum of Madrasah Aliyah toward gender equity. This condition has been misunderstood by some scholars that Hadith does not support gender equity. The aims of this paper are to give a clear picture of gender equity in Hadith literature and analyze the content of Hadith Curriculum of Madrasah Aliyah in Indonesia in relation to gender equity support. This research applied descriptive analytic method. Data were gained through Hadith literature and Hadith Curriculum of Madrasah Aliyah, Year 2013. This study revealed that Hadith strongly support gender equity in all aspects of life achieved as in economic, social, and political aspects. In addition, Hadith Curriculum of Madrasah Aliyah does not strongly support the emergence of strong and positive thinking toward gender equity among the students of Madrasah Aliyah most of whom then becoming religious leaders in Indonesian society. The implication of this finding requires us to make changes in the content structure of the Curriculum of Hadith for Madrasah Aliyah in Indonesia.